Kajian Tingkat Keparahan Postur Janggal yang Berkontribusi kepada Gangguan Sistem Muskuloskeletal (Studi Pustaka Naratif) - Safhira, Ira; Satrya, Chandra (National Journal of Occupational Health and Safety, 2021)
Background: Not all of awkward postures that exist in the industry should be eliminated. Due to the fact, awkward posture can not be separated from daily work activities. Any movement that makes the body angle away from the normal position, can be said to be an awkward posture. Misconceptions related to the concept of awkward posture are followed by the fact that the assessment’s concepts of the observation method that are often used to assess awkward postures (REBA, RULA, and OWAS) is not accordance with the theory it should be. That condition can reduce the effectiveness of controlling musculoskeletal system disorders. To overcome this, it is necessary to review the literature that explains what variables can affect the severity of awkward postures. Method: This study uses a narrative literature review method with the aim is for describing the relationship between duration, frequency, and angle inclination of posture with the severity of awkward postures. Results: 15 literatures were obtained from the online databases of Science Direct, ProQuest, and Google Scholar, with details of 9 literatures using the semi-experimental method, 5 literatures using the cross sectional method, and 1 literature using the systematic literature study method. Conclusion: Based on results of the literature, there are some evidences that proof the linear relationship between the duration, frequency, and angle inclination of postures with the severity of awkward postures.